Revalidation of the academic quality of life questionnaire for students attending portuguese polytechnic higher education institutions - Ferreira, Manuela (2019)
Introduction: School dropout is a problem that affects higher education and the schools that are part of this educational system. School dropout has increased over time and is closely connected with students’ Quality of Academic Life. Objectives: To test the factorial structure of the Questionnaire of Academic Experience for Portuguese higher education students. Methodology: Quantitative, cross-sectional, descriptive and correlational study. A student socio-demographic background questionnaire and Almeida Soares and Ferreira’s Academic Experiences Questionnaire (QAE) (2002) were used as data collection instruments. The sample consists of 891 students aged between 17 and 40 years, with a mean age of 19.68 years (± 2.34 years). Results: The QAE designed by Almeida, et al. (2002), after validation, was composed of 35 items. Confirmatory factorial analysis demonstrates the validity of its structure in five dimensions: personal, study, interpersonal, career and institutional. Statistics on Quality of Academic Life have an average index of 60.46%; ± 10.02 sd. Female students show higher rates in dimensions such as: personal quality of life, profession/career, study, institutional, and overall quality of life. Male students show higher mean values in the quality of life, interpersonal and career dimensions Conclusions: The results of the present study support the psychometric adequacy of the QAE Almeida, et al. (2002) designed for the Portuguese population, indicating that it can be used in tests conducted in this field of knowledge.